Tablet misoprostol as a cervical priming agent prior to surgical abortion - Revankar, Vijaya Manohar; T. N., Harsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Every effort to promote effective contraceptive methods as well as emergency contraception is being made, still there would be a need and place for termination of pregnancy. Objective of present study was to evaluate and to know the efficacy and adverse effects of tablet misoprostol 400 micro gram as a cervical priming agent administered either by oral or vaginal route, 3 hours before MTP. Methods: Prospective randomized not blinded study carried out for two years at Government Tertiary care level hospital, OBG Department, Mangalore on 100 women with gestational age up to 12 weeks requesting for surgical abortion. Results: In both the groups there was no significant statistical difference with respect to age (p=0.44), parity and gestational age (p=0.59). With respect to baseline cervical dilatation significant statistical difference was not observed in both the groups. Baseline dilatation of the cervix was 8.0 mm versus 8.2 mm (p value=0.55). Baseline cervical dilatation was ≥7mm in 90% of women when tab misoprostol was given by oral route and 94% with vaginal route. There was no significant statistical difference with respect to side effects (p value>0.05) except nausea (p=0.01) found in both the groups. Gastro Intestinal side effects were more in oral misoprostol group, but it was not statistically significant. Conclusions: Oral route is an effective alternative to vaginal route. Oral route is preferred over vaginal route because women can do self-administration at home and there was no internal examination discomfort.